2014
DOI: 10.1111/mpp.12124
|View full text |Cite
|
Sign up to set email alerts
|

Sequence diversity in the large subunit of RNA polymerase I contributes to Mefenoxam insensitivity in Phytophthora infestans

Abstract: Phenylamide fungicides have been widely used for the control of oomycete-incited plant diseases for over 30 years. Insensitivity to this chemical class of fungicide was recorded early in its usage history, but the precise protein(s) conditioning insensitivity has proven difficult to determine. To determine the genetic basis of insensitivity and to inform strategies for the cloning of the gene(s) responsible, genetic crosses were established between Mefenoxam sensitive and intermediate insensitive isolates of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 65 publications
2
64
0
2
Order By: Relevance
“…It has been suggested that resistance to metalaxyl in P. infestans is controlled by only one or two major loci in close proximity, along with a host of minor genes. One such locus has recently been identified in the large subunit of RNA polymerase I (Randall et al ., ). This hypothesis is consistent with the pattern of resistance observed in the isolates of the present study, where most isolates fell into the two extremes of highly sensitive with an IC 50 below 1, or highly resistant with an IC 50 above 500 (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that resistance to metalaxyl in P. infestans is controlled by only one or two major loci in close proximity, along with a host of minor genes. One such locus has recently been identified in the large subunit of RNA polymerase I (Randall et al ., ). This hypothesis is consistent with the pattern of resistance observed in the isolates of the present study, where most isolates fell into the two extremes of highly sensitive with an IC 50 below 1, or highly resistant with an IC 50 above 500 (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, sequence diversity in the large subunit of RNA polymerase I has been analysed recently using isolates of Phytophthora infestans (Mont.) de Bary, insensitive to the oomycete fungicide mefenoxam, and the association of one single nucleotide polymorphism in subunit RPA190 with insensitivity to this fungicide has been found . The authors pointed out the possibility that insensitivity to mefenoxam might have arisen on multiple occasions in different pathogen genotypes, leading to independent SNPs encoding changes responsible for insensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The phenylamide metalaxyl was one of the first chemicals to exhibit specificity to oomycetes. Soon after its introduction and widespread use, fully insensitive strains emerged, but only 35 years later was the molecular basis of this insensitivity uncovered (Randall et al ., ). Mining of the P. infestans genome has revealed many novel proteins with domain combinations that are unique to oomycetes (Seidl et al ., ).…”
Section: Phytophthora Infestansmentioning
confidence: 99%